The stuff of life : a graphic guide to genetics and DNA - Schultz, Mark, 1955-; Cannon, Kevin; Cannon, Zander (New York : Hill and Wang, 2009)
Bloort 183, an asexual alien scientist, explains the fundamentals of genetics, covering human DNA, evolution, and other scientific concepts in graphic novel format.
"A graphic novel from Hill and Wang.".
Includes bibliographical references (p. 145).
Booklist.
Adult
Keywords: DNA -- Comic books, strips, etc; Genetics -- Comic books, strips, etc; Comic books, strips, etc; DNA -- Comic books, strips, etc; Genetics -- Comic books, strips, etc